Novel degradation of amoxicillin by WO3/Ag3VO4 Z-scheme heterojunction deposited on rGO - Mai Hung Thanh Tung; Tran Thi Thu Phuong; Dinh My Ngoc Tram; Do Minh The; Nguyen Vu Ngoc Mai; Tran Thi Thu Hien; Le Thi Cam Nhung; Nguyen Thi Thanh Binh; Cao Van Hoang; Dao Ngoc Nhiem; Thanh-Dong Pham; Nguyen Thi Dieu Cam (My University, 2022)
Novel degradation of amoxicillin by WO3/Ag3VO4 Z-scheme heterojunction deposited on rGO
Keywords: WO3/Ag3VO4